(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2014)
Objective: The authors present their experiences in the management of xtradural haematoma in children which involved an aggressive diagnostic approach, prompt surgical evacuation of the haematoma results in an excellent outcome. Subjects and methods: 138 consecutive patients with cranial extradural haematoma who underwent surgery in department of Neurosurgery from 1st January 2006 to 31st July 2009 were included in this prospective study. Each of the patients were evaluated in term of age, sex, mode of injury, localization of haematoma, clinical presentation, CT findings, operative measures and outcome. Results: Out of 138 cases 72.47 % were boys and 13.78 % were girls. The boys and girls ratio was 2.64: 1. Age ranges from 1.8 to 15 years with a mean age of 9.49 years. Most of the victims are in first half of second decade of life and closely followed by the 5-10 years age group. The most common mode of injury was fall 40.58 %, (n = 56) followed by Road traffic Accident (RTA) 31.89 %, (n = 44) .The Most common clinical presentation was altered sensorium 59.43 %, (n = 82), followed by Headache / Vomiting 56.53 %, (n = 78). Conclusion: Extradural haematoma in children is a recognized and one of the most rewarding neurosurgical emergencies. It must be recognized and evacuate early to prevent potential mortality and morbidity. Many factors affect the outcome of extradural haematoma surgery. In addition to influence of presence cranial fractures, associated brain lesions and pre-operative neurological condition of patient, duration of time interval between onset of coma and surgical intervention, morbidity and mortality have also been shown to be affected by age with better prognosis in patients under 10 years of age. DOI: http://dx.doi.org/10.3329/jpsb.v1i1.19450